DESEMPENHO AGRONOMICO DE POPULAÇÕES F4 DE SOJA EM AQUIDAUNA, MATO GROSSO DO SUL - Pires Nepomuceno , Romeu; Eduardo Torres , Francisco; dos Santos Leite , Michele; Guilherme Romaike Catto, João; Rati Minatto , Marcela; Burema Oliveira , Jacyeli (ANAIS DO ENIC, 2026)
-